How Usable Are the Learning Management Systems? The Users Have their Say - M.M. Althobaiti; P. Mayhew (European Alliance for Innovation (EAI), 2016)
E-learning is an innovative way of learning that is both symbolic and derivative of 'the information age.' When used as part of the learning process, it provides users with greater flexibility in terms of time and location. For an E-learning application to be considered effective, it should provide its users with a certain standard of usability; otherwise, the learning process is likely to become cumbersome and frustrating for the learner. Focusing on this dilemma, this paper aims to assess the usability of the Jusur Learning Management System (LMS) that is used in higher education in Saudi Arabia. Nine factors have been incorporated into a survey to evaluate the system: content, learning and support, visual design, navigation, accessibility, interactivity, selfassessment, learnability, and motivation. The results show that E-learners who use the Jusur LMS tend to find that Jusur is a usable and desirable application in terms of its users' experiences and perspectives.